Housing prices and affordability issues among local people in Malaysia: a case study of the Perak State, Malaysia - Mohamed Osman, Mariana; Shuid, Syafiee; Bachok, Syahriah; Khalid, Najihan (2016)
The objective of this paper is to determine factor influencing housing price in Perak. The study found that there are five factors which influenced the drastic increases in housing price in Perak. Factors identified namely the absence of control and monitoring of housing project, developers’ tendency to develop land on piecemeal, the independent market policies that exposed to the speculative demand and profit investment maximization, the increase in construction cost, and the development of the new township. Besides that, the study used clustered convenience sampling questionnaire survey of 1,371 respondents in various districts in Perak to identify the affordability level of Perakian. Findings from analysis found that the most affordable house price should be below RM 140,000 for people income less than RM4,000. The existing state housing policy should be improved, where the requirement units for low cost, medium cost and the affordable house should be based on the local needs. Finally, the requirement of affordable housing units should differ based on this affordability level due to the differences in median income of the people in each district.